Penanaman Pohon Sebagai Bentuk Edukasi Lingkungan Di Wilayah Kelurahan Penurunan Kota Bengkulu - Aisyah, Amanda Putri; Muda’ I, Ihtiar Dayu; Pratama, Aldi Rizki; Lestari, Tiara Oktavina; Handayani, Sri; Aprianto, Sandi; Susena, Karona Cahya (Jurnal Dehasen Untuk Negeri, 2026)
Environmental degradation in Penurunan Subdistrict, Bengkulu City is partly caused by the lack of green spaces and low public awareness of environmental conservation. This community service activity aims to increase public awareness through a tree planting program as a form of environmental education. The methods used include socialization, tree planting practice, and community assistance, especially involving children as agents of change.The results show increased understanding of the benefits of trees in improving air quality, preventing flooding, and enhancing environmental comfort. Community participation also grew, creating a sense of responsibility for maintaining the planted trees. This program is expected to create a greener, healthier, and more sustainable environment.